Installments, Social Networks, and Tarot Card Spreads: How Loyalty Support Strategies Work in the Modern Digitalized Russian Esoteric Market - Zharakhovich, Maria (International journal for the study of new religions, 2023)
This study identifies strategies for maintaining consumer loyalty among esoteric specialists in Russia's digital market. Employing a mixed-methods approach, we conducted 20 semi-structured interviews with online esoteric practitioners and analyzed 150 Telegram channels (50 each for tarologists, magicians, and astrologers) between March and May 2024. Thematic coding and quantitative content analysis were used to examine loyalty strategies. Results indicate that specialists employ two main approaches: increasing customer engagement through profitable deals, multichannel communication, personalization, and image-making; and creating value for clients by offering referral programs, client communities, webinars, live broadcasts, esoteric courses, and feedback mechanisms. Notably, webinars and live broadcasts are utilized as part of broader strategies to deepen client engagement and foster community rather than as stand-alone tactics. This research highlights how digitalization reshapes loyalty strategies in the esoteric services market, emphasizing the importance of both engagement and value creation.